STRATEGI POLITIK GALIH RAKASIWI PADA PEMILIHAN KEPALA DESA LIMUSNUNGGAL KECAMATAN CILEUNGSI KABUPATEN BOGOR PADA TAHUN 2020 - Rosari Angelica Gurning (2023)
This study aims to find out how Galih Rakasiwi's political strategy is in the 2020 election for the Head of Limusnunggal Village, Cileungsi District, Bogor Regency, using several theories, including political strategy, local politics, and democracy. This political strategy research also uses 10 indicators to see how the political strategy is implemented, the indicators are: 1. Mission formulation, 2. Situational assessment and evaluation, 3. Sub-strategy formulation, 4. Target formulation, 5. Target image, 6. Groups, 7. Target group messages, 8. Key instruments, 9. Strategy implementation, 10. Strategy controls. The method used in this study is a qualitative method with a descriptive approach, where the data used are primary and secondary data obtained through interviews and documentation. In analyzing the data, the technique used is data reduction, data display, triangulation, and conclusion. The results of this study indicate that Galih Rakasiwi has a goal of improving the welfare of the residents of Limusnunggal Village by focusing his vision and mission on issues of concern to Limusnunggal Village, namely issues regarding Health, Education, Employment, Public Services. Apart from that, there is a weakness where Galih Rakasiwi is that he is the youngest candidate among the other candidates, and this has been overcome by Galih Rakasiwi and the Shalih Team by doing a lot of outreach to the community. Apart from that, Galih also carried out activities to absorb the aspirations of the villagers and was accommodated and promised solutions. In every strategic activity he does not overdo it, he only monitors the opponent's movements and embraces all groups.